Cintura hipertrigliceridémica en mujeres pre y postmenopáusicas de trujillo 2011 - 2012 - Villarreal González, Mery Nancy (2013)
The overweight and obesity that menopausal women develop mean an increase in the waist circumference which is mainly related to hypertriglyceridemia, these two conditions being the pathogenic nucleus of the metabolic syndrome. Objectives: To compare the frequency of Hypertriglyceridemic Waist (CHT) in pre and postmenopausal women. Material and method: Cross-sectional and analytical study. It included 140 women, 70 premenopausal women and 70 postmenopausal women between the ages of 40 and 65 from July 2011 to December 2012. The selection was based on inclusion and exclusion criteria. Weight, height and Waist circumference, according to international recommended protocols. Hypertriglyceridemic waist circumference was considered if waist circumference was greater than or equal to 80cm and triglycerides greater or equal to 150 mg / dl. Results: The frequency of CHT in premenopausal women was 35.7% and in postmenopausal women it was 38.57%. The OR was 1.13 with 95% CI of 0.569 to 2.244 and p of 0.8611. Conclusions: Menopause does not affect hypertriglyceridemic waist circumference